VOC : A Bibliography of Publications Relating to the Dutch East India Company, 1602-1800 - Landwehr, John, (European History and Culture - Book Archive pre-2000., 1991)
At the height of its power and influence in the seventeenth and eighteenth century the VOC - acronym for the United Netherland East India Company - was the greatest commercial concern in the world. The scope of its activities extended from the Cape of Good Hope to Japan. In some aspects, the Baltic trade and the North Sea fisheries were of more fundamental relevance for the economy of the Lowlands. But it was the more spectacular East Indian trade which aroused the admiration and the envy of foreigners, sometimes to the point of war. In this bibliography several topics are covered. Not only technical matters such as the legal status of the VOC, its management, directors and shareholders, but also subjects as voyages, battles, ship building, navigation, geography, natural history, ethnography, mission work, ministration, and many others. With 1674 entries, fully described and fully indexed.